Performance evaluation of multiple-beam free space optics in tropical rainy weather - Al-Gailani, Samir A.; Mohd Shah, Nor Shahida; Salem, Ali Ahmed; Algeelani, Nasir A.; Bantahar, Mohammed A. (IEEE, 2021)
Free space optics (FSO) has the potential to replace optical fiber as a solution for the last mile problem. FSO is favored because of its cheap maintenance costs and quick deployment time as compared to other communication system such as fiber optics. Atmospheric attenuation is a problem for FSOs with classic single beam systems, especially when it rains heavily specially in tropical region like Malaysia. As a result, a multibeam FSO transceiver system has become popular as a solution to this problem. The purpose of this study is to compare the standard single beam FSO system with the suggested multibeam FSO system. At a bit error rate (BER) of 10-9, the comparison is made in terms of received optical power, channel distance, and geometrical losses. Rain intensity data is gathered over a six-month period. To evaluate the performance of both systems, the average rain attenuation is calculated from this data and exposed to single beam and multibeam FSO systems. The multibeam FSO approach was found to increase the system's performance. The results show that employing up to four beams improves the quality of received power and increases the channel distance to 1150 m when compared to a single beam FSO system with a channel distance of only 830 m.